PENINGKATAN PRODUKTIVITAS MELALUI PENINGKATAN KUALITAS KERJA, KEPEMIMPINAN, DAN KOMPENSASI PADA PT. KMK GLOBAL SPORTS - Prasetya, Wibawa; Chandra, Andrey (E-Journal Widya Ekonomika, 2017)
To increase the productivity of the company, required not only the factor of human resources (HR) who are good and have the ability, but is also influenced by factors such as leadership, compensation and quality of work. The purpose of this research is to know the: (1) the influence of leadership on quality of work and productivity, (2) the influence of compensation to quality of work and productivity, and (3) the influence of the quality of work to productivity. The research conducted at the PT. KMK Global Sports with a total population of 1498 people and the number of samples taken 200 people, chosen by purposive. The processing techniques and data analysis using the Structural Equation Modeling (SEM) software with amos 22.0. The results showed that: (1) influential leadership significantly to quality of work, but the effect was not significant to productivity (2) compensation effect significantly to the quality of work and productivity, (3) the quality of the work of influential significantly to productivity.